2013
DOI: 10.1111/faf.12013
|View full text |Cite
|
Sign up to set email alerts
|

Primary productivity demands of global fishing fleets

Abstract: To be sustainable, the extractive process of fishing requires biomass renewal via primary production driven by solar energy. Primary production required (PPR) estimates how much primary production is needed to replace the biomass of fisheries landings removed from marine ecosystems. Here, we examine the historical fishing behaviour of global fishing fleets, which parts of the food web they rely on, which ecosystems they fish and how intensively. Highly mobile European and Asian fleets have moved to ever more d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 51 publications
0
52
0
Order By: Relevance
“…Reducing trophic levels by only 14% for secondary consumers and above can bring fisheries in balance with primary productivity (reproducing ref. 46; SI Appendix); our model predicted changes in trophic level of up to 27% for species like largehead hairtail from those used in Watson et al (46). If China's fishery catch data are roughly correct, they appear to have, perhaps unwittingly, performed the world's largest experiment in marine predator removal with the result of increases in harvestable biomass.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Reducing trophic levels by only 14% for secondary consumers and above can bring fisheries in balance with primary productivity (reproducing ref. 46; SI Appendix); our model predicted changes in trophic level of up to 27% for species like largehead hairtail from those used in Watson et al (46). If China's fishery catch data are roughly correct, they appear to have, perhaps unwittingly, performed the world's largest experiment in marine predator removal with the result of increases in harvestable biomass.…”
Section: Resultsmentioning
confidence: 79%
“…For example, it has recently been suggested that the catch extracted from the East China Sea exceeds the potential of the input primary productivity (46), which implies unsustainable fishing at the ecosystem level. The age structure for most fished populations in the East China Sea consists largely of 1-y-olds and exploitation rates in the fisheries appear to be very high (47), which suggests decreasing harvest rates could result in large benefits [from the perspective of single-species assessment methods (48)].…”
Section: China's Fisheriesmentioning
confidence: 99%
“…Although fishing has expanded offshore in recent decades, degrading a number of high value stocks (54), catch outside LMEs remains below 9% of the global total in all years. Offshore effort and ecosystem-level exploitation per area also generally remains far less than in coastal regions (55,56). This is in part a reflection of the high capital cost of high-seas fishing that restricts this activity to a select subset of nations (57).…”
Section: Discussionmentioning
confidence: 99%
“…Overfishing alters marine population demographics (removal of older individuals), spatial dynamics (changes in spawning grounds) and species abundance and thus reduces the ocean's ability to provide food, maintain water quality and recover from perturbations (Worm et al 2006;Rockström et al 2009a;Watson et al 2014). Historic exploitation of sea otters in the Aleutian Islands removed the primary predator of sea urchins, resulting in massive deforestation of kelp forests via an unregulated sea urchin population (Steneck et al 2002).…”
Section: Other Environmentalmentioning
confidence: 99%